Synthesis Of Ultrafine Particles Of Aluminum Nitride By Evaporation Of Aluminum In Argon + Ammonia Gas Mixture - Seiji Yokoyama (The Minerals, Metals and Materials Society, 2006)
As a series of fundamental study on the gas evaporation method, a levitation-melted aluminum was evaporated in the gas mixture of argon and ammonia to synthesize ultrafine particles of aluminum nitride. When the ammonia partial pressure were more than 2kPa, the formation ratio of aluminum nitride was about 95%. The particles of aluminum nitride were mainly hexagonal. The mean size of the particles of aluminum nitride was about 57 nm, and it was constant without depending on the temperature of the levitated aluminum and the partial pressure pf ammonia. The aluminum nitride was formed by the reaction between ammonia and condensed liquid aluminum particle whose size was relatively small.